'Look who's got a case of dark prince envy': Dracula, televisuality and the golden age(s) of TV horror. Issue 2 (1st October 2017) - Abbott, Stacey
While Dracula's presence within the cinema has fuelled extensive scholarship, little attention has been played to his role within television. Where television adaptations are discussed, the analyses are primarily removed from their televisual contexts or discussed as anachronistic, their televisuality used to reaffirm the notion that within a world of modern horrors, Dracula is not scary any more. In contrast, this article examines the relationship between Dracula and television with a specific focus upon Dracula's contribution to a changing landscape of televisual horror. The article focuses its analysis upon two key periods of TV horror – 1950s–1970s and post-2000 – examining the role that Dracula plays on TV and considering how it embodies the increasingly provocative nature of horror. It examines the role that Dracula plays within children's, family and prestige drama. It considers how Dracula adaptations interrogate the uncanniness of the televisual medium. It examines the impact of the seeming over-familiarization of Stoker's Count by challenging the perception that this familiarity has neutered Dracula as an icon of horror. Instead the article argues that television offers a space in which Dracula continues to function as horror, destabilizing questions of normality and the comforts of quality television programming.